As disputas em torno da tese kantiana da irrealidade do tempo: análise e avaliação da doutrina do tempo na Dissertação de 1770 e na Crítica da razão pura a partir das objeções de Lambert, de Mendelssohn e de Trendelenburg - Chabbouh Junior, Marco Antonio (2018)
In the dissertation On the form and principles of the sensible and the intelligible world, Immanuel Kant formulates for the first time the thesis that was considered the mark of his critical turn: the thesis that time (and space) is ideal. In the same year, two of his most influential contemporaries objected to one of the central points of the newly formulated theory: Johann Heinrich Lambert and Moses Mendelssohn could not accept that time was unreal. Almost a century later, Adolf Trendelenburg formulated an important critique that shaped the way that the "Transcendental Aesthetics" would be read by the interpreters of Kant's philosophy. The purpose of this work is to discuss Kant's philosophy of time in the light of these objections and to evaluate if Kant’s main thesis concerning the nature of time is sustainable. For this, three points need to be discussed: (i) the thesis of the unreality of time in 1770 and the objections presented that year; (ii) Kant's reception of these objections and possible changes in the doctrine presented in the mature text of the Critique of Pure Reason and; (iii) the degree of sustainability of the Kantian philosophy of time in confrontation with Trendelenburg’s objection. Through this discussion and through an analysis of the development of a certain English-speaking interpretative tradition, it will be seen that the debate between Kant, Lambert, Mendelssohn and Trendelenburg can be reduced to the debate between the philosopher of Königsberg and his main opponents in the "Transcendental Aesthetics”, namely, Newton and Leibniz. It will also be shown by this reduction that Kant’s mature philosophy of time is coherent and sustainable even in the face of the renowned critics and even adopting the interpretative structure used by Trendelenburg